Issues of legislative support for sustainable public procurement in the Republic of Kazakhstan - Bukhaeva, A.A.; Y.M. , Aytkazin (Bulletin of the Karaganda University “Law Series”, 2024)
The article provides an overview of the legal framework for the implementation of procurement for public needs, taking into account the economic, environmental and social aspects or the functioning of «sustainable public procurement» in the country. The use of sustainable public procurement is gaining momentum around the world. Over the last decade, many countries have adopted laws encouraging the development of these types of procurement. Kazakhstan is not lagging behind this trend and continues to try to improve its legislation. Despite the good intentions of the discussed draft law on «changing the course» in the sphere of public procurement, several questions remain unclear as to how the legislative changes will be implemented in practice. And the current legislation contains only certain components of sustainable public procurement. Therefore, in order to review the legislation of the Republic of Kazakhstan regulating the sphere of public procurement from the point of view of using the principles of sustainable public procurement, to assess its practical application, as well as to study the possibilities of legislative support of the concept of sustainable public procurement in general, the group of authors of this article analyzed the current legislation. Taking into account the new draft law under discussion, they made forecasts on the development of these institutions in the country, as well as considered successful practices of foreign countries. The authors of the article came to the conclusion that taking into account the fact that regular public procurement is an important tool for ensuring environmental safety, solving economic and social problems, its wide application in Kazakhstan is an important necessity. Necessary measures for development and improvement of legislation in this sector are proposed.